La tutoría como un factor influyente en la identidad profesional del alumno de pregrado de medicina. - Vives Varela, Tania; Salazar Hernández, Daniela Hazel (Revista de la Facultad de Medicina de la UNAM)
Introduction: the formation of the medical professional identity is achieved in stages during which the characteristics, values and norms of the medical profession are internalized, which results in the individual thinking, acting and feeling like a doctor. Tutors in medicine should clarify and encourage the principles within study programs and learning environments in order to support the formation of the professional identity of their students. Objective: the purpose of this paper is to reveal the participation of medical tutoring as one of the most influential factors that contribute to the development of the professional identity of medical students, as well as to give some guidelines so that the training of tutors. It contemplates tools that allow them to contribute to the positive and valued construction of the professional identity of the students.